Structural Basis of Outstanding Multivalent Effects in Jack Bean α‐Mannosidase Inhibition. Issue 27 (6th June 2018) - Howard, Eduardo; Cousido‐Siah, Alexandra; Lepage, Mathieu L.; Schneider, Jérémy P.; Bodlenner, Anne; Mitschler, André; Meli, Alessandra; Izzo, Irene; Alvarez, H. Ariel; Podjarny, Alberto; Compain, Philippe
Abstract: Multivalent design of glycosidase inhibitors is a promising strategy for the treatment of diseases involving enzymatic hydrolysis of glycosidic bonds in carbohydrates. An essential prerequisite for successful applications is the atomic‐level understanding of how outstanding binding enhancement occurs with multivalent inhibitors. Herein we report the first high‐resolution crystal structures of the Jack bean α‐mannosidase (JBα‐man) in apo and inhibited states. The three‐dimensional structure of JBα‐man in complex with the multimeric cyclopeptoid‐based inhibitor displaying the largest binding enhancements reported so far provides decisive insight into the molecular mechanisms underlying multivalent effects in glycosidase inhibition. Abstract : Sweet sandwich ! High‐resolution crystal structures of Jack bean α‐mannosidase (JBα‐man) in apo and inhibited states provided decisive insight into the way a glycosidase and a multimeric inhibitor interact to produce outstanding multivalent inhibitory effects. Four ordered iminosugar heads of a 36‐valent inhibitor (cyan in the picture) simultaneously engaged all four active sites of two dimeric JBα‐man molecules to form a strong sandwich chelate complex.